2011
DOI: 10.1152/jn.00193.2011
|View full text |Cite
|
Sign up to set email alerts
|

Between-subject variance in the magnitude of corticomuscular coherence during tonic isometric contraction of the tibialis anterior muscle in healthy young adults

Abstract: Ushiba J. Between-subject variance in the magnitude of corticomuscular coherence during tonic isometric contraction of the tibialis anterior muscle in healthy young adults. J Neurophysiol 106: 1379-1388, 2011. First published June 8, 2011 doi:10.1152/jn.00193.2011.-Oscillatory activity of the sensorimotor cortex has been reported to show coherence with muscle activity in the 15-to 35-Hz frequency band (␤-band) during weak to moderate intensity of isometric contraction. The present study examined the variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 59 publications
5
37
0
Order By: Relevance
“…Finally, a large downside for the potential clinical application of CMC is that it cannot be detected in all cases: even healthy subjects, with normal voluntary motor control, do not all present CMC (Ushiyama et al. 2011; Mendez-Balbuena et al. 2011; Campfens et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a large downside for the potential clinical application of CMC is that it cannot be detected in all cases: even healthy subjects, with normal voluntary motor control, do not all present CMC (Ushiyama et al. 2011; Mendez-Balbuena et al. 2011; Campfens et al.…”
Section: Introductionmentioning
confidence: 99%
“…The inter-individual difference in the presence of CMC reflects physiological inter-individual differences in the strength of the oscillatory corticomuscular coupling and is not the result of technical aspects such as the (mis-) placement of EEG electrodes (Ushiyama et al. 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Corticomuscular coherence (CMC) has been considered to reflect the mutual interaction between the sensorimotor cortex and contracting muscles via descending motor pathways and ascending somatosensory pathways34567. Recently, we have reported that the magnitude of CMC varies among individuals even in healthy young adults8910. However, the physiological mechanisms underlying the inter-individual differences in CMC are still unclear.…”
mentioning
confidence: 99%
“…However, the physiological mechanisms underlying the inter-individual differences in CMC are still unclear. Although the inter-individual differences include some technical limitations for EEG/EMG, we believe that it is valuable to examine the physiological mechanisms behind inter-individual differences in CMC, since CMC is associated with insensible personal behaviour such as force steadiness10 and reaction time11.…”
mentioning
confidence: 99%
“…Tecchio et al reported patients’ exaggerated and bilaterally coupled cortico-muscular coherence in the beta band (mean frequency 21.5 Hz) during isometric contraction [16], which is not seen in healthy participants (e.g. [17]). These studies suggest the existence of different mechanisms of cortico-muscular coupling from healthy individuals in dystonia patients.…”
Section: Resultsmentioning
confidence: 99%